The Effect of ICU Diaries on Psychological Outcomes and Quality of Life of Survivors of Critical Illness and Their Relatives: A Systematic Review and Meta-Analysis. Issue 2 (February 2019) - McIlroy, Philippa A.; King, Rebecca S.; Garrouste-Orgeas, Maité; Tabah, Alexis; Ramanan, Mahesh
Abstract : Objectives: To evaluate the effect of ICU diaries on posttraumatic stress disorder symptoms in ICU survivors and their relatives. Secondary objectives were to determine the effect on anxiety, depression, and health-related quality of life in patients and their relatives. Data Sources: We searched online databases, trial registries, and references of relevant articles. Study Selection: Studies were included if there was an ICU diary intervention group which was compared with a group without a diary. Data Extraction: Titles, abstracts, and full-text articles were reviewed independently by two authors. Data was abstracted using a structured template. Data Synthesis: Our search identified 1, 790 articles and retained eight studies for inclusion in the analysis. Pooled results found no significant reduction in patients' posttraumatic stress disorder symptoms with ICU diaries (risk ratio, 0.75 [0.3–1.73]; p = 0.5; n = 3 studies); however, there was a significant improvement in patients' anxiety (risk ratio, 0.32 [0.12, 0.86]; p = 0.02; n = 2 studies) and depression (risk ratio, 0.39 [0.17–0.87]; p = 0.02; n = 2 studies) symptoms. Two studies reported significant improvement in posttraumatic stress disorder symptoms of relatives of ICU survivors; however, these results could not be pooled due to reporting differences. One study reported no significant improvement in either anxiety (risk ratio, 0.94; 95% [0.66–1.33]; p = 0.72) or depression (risk ratio, 0.98; 95% [0.5–1.9]; p = 0.95) in relatives. There was a significant improvement in health-related quality of life of patients with a mean increase in the Short Form-36 general health score by 11.46 (95% CI, 5.87–17.05; p ⩽ 0.0001; n = 2 studies). No studies addressed health-related quality of life of relatives. Conclusions: ICU diaries decrease anxiety and depression and improve health-related quality of life, but not posttraumatic stress disorder among ICU survivors and may result in less posttraumatic stress disorder among relatives of ICU patients. Multicenter trials with larger sample sizes are necessary to confirm these findings. Abstract : Supplemental Digital Content is available in the text.